PREVALENCE AND PATTERN OF UTERINE BLEEDING AMONG BREASTFEEDING WOMEN USING PROGESTERONE-ONLY PILLS - Prima Dhewi Ratrikaningtyas; Dian Rosdiana; Siswanto Agus Wilopo (Public Health of Indonesia)
Background: Progesterone-Only Pill (POPs) is one of the ideal oral contraceptive methods for breastfeeding women. Discontinuation of POPs was mostly due to bleeding pattern disorders.